Integrating sustainability reporting into enterprise risk management and its relationship with business performance: A conceptual framework - Shad, M.K. (2019)
This paper conceptualises a framework that examines the moderating effect of sustainability reporting practices on the relationship between enterprise risk management (ERM) implementation and business performance. Business performance is proxied through a value-added measurement technique, namely the economic value added (EVA). An Effective ERM adoption has a significant positive impact on businesses' overall performance. However, there are limited studies conducted on ERM implementation and how sustainability reporting could influence organisations' performance through ERM. Many business organisations globally do not incorporate sustainability initiatives within their corporate strategy, whereas they should be critical input for strategic management and corporate planning. By combining the Stakeholders Theory and the Modern Portfolio Theory, this study integrates ERM implementation with sustainability reporting to examine their effect on business performance's economic value added. This paper proposes a quantitative content analysis of the of the annual reports to obtain information about companies' enterprise risk management practices and sustainability reporting. While secondary data related to the economic value added (EVA) measurement will be extracted from Thomson Reuters DataStream. The paper proposes ordinary least square (OLS) for the proposed analysis. The conceptual model espoused by this study will provide insights in formulating strategies and serve as an important conduit to enhance the EVA performance especially of the oil and gas companies. The EVA performance can be achieved through the improvement of price to earnings ratios and the reduction of cost of capital by reducing information asymmetry among the business, the insurance companies, the lenders and the shareholders of the company.